Kualifikasi Alasan-Alasan Tertentu Menurut Pasal 3 Angka 15 Perubahan Kode Etik Notaris - Ratihtiari, Anak Agung Titah; Bagiastra, I Nyoman (Acta Comitas; Vol 6 No 03 (2021)DO - 10.24843/AC.2021.v06.i03.p12, 2021)
Abstract The purpose of this study is to find out what is included in the qualifications of certain reasons in Article 3 point 15 of the Amandment to the Notary Code of Ethics which states that “Notaries are obliged to carry out the position of a Notary in their office, except for certain reasons that carried out to the outside of the office to create the legal certainty.” The research using normative legal research methods. The results of this study indicate that the meaning of certain reasons in Article 3 point 15 is a condition that is permissible and doesn’t violate the provisions of Notary public Law or Amandments to the Notary Code of Ethics. Things that can be classified as qualifying of the certain reasons are related to the making of a relaas deed which is generally made outside the office and if the client is in a bad condition and not possible to leave the house or hospital to come to the Notary’s office. Furthermore, the violation of the provisions of Article 3 point 15 doesn’t necessarily affect the authenticity of the authentic deed. Abstrak Tujuan penelitian ini untuk mengetahui apa saja yang termasuk ke dalam kualifikasi alasan-alasan tertentu dalam Pasal 3 angka 15 Perubahan Kode Etik Notaris yang menyatakan bahwa “Notaris wajib menjalankan jabatan Notaris di kantornya, kecuali alasan-alasan tertentu yang dilakukan tidak dalam kantor Notaris sehingga terciptanya kepastian hukum.” Penelitian ini menggunakan metode penelitian hukum normatif. Hasil penelitian menunjukkan bahwa arti dari alasan-alasan tertentu pada Pasal 3 angka 15 KEN-P merupakan keadaan yang dibolehkan serta tidak melanggar peraturan UUJN ataupun KEN. Hal yang dapat digolongkan dalam kualifikasi alasan-alasan tertentu yaitu berkaitan dengan dibuatnya akta relaas yang pada umumnya memang dibuat di luar kantor serta apabila klien atau penghadap Notaris sedang sakit yang kemudian tak dimungkinkan untuk keluar rumah ataupun rumah sakit demi datang ke kantor Notaris. Selanjutnya pelanggaran Pasal 3 angka 15 KEN-P belum tentu mempengaruhi otentisitas akta.